Maxillofacial brown tumor due to secondary hyperparathyroidism in a chronic kidney disease patient: Report of a rare case with a review of its pathogenesis - Debasish Pramanick; Ranjan Ghosh; Jayanta Saha (Journal of Oral Research and Review)
Hyperparathyroidism (HPT) (hypersecretion of parathyroid hormone) may be primary, secondary, or tertiary. Primary HPT (PHPT) is usually associated with parathyroid hyperplasia or neoplasms. Secondary HPT (SHPT) develops when there are continuous low levels of serum calcium in chronic kidney disease (CKD) patients who can’t uptake calcium from the gut due to insufficient production of calcitriol. Tertiary HPT develops in a long-standing case of SHPT. Brown tumor is a benign bone lesion seen in both PHPT and SHPT, up to 4.5% and 1.5%–1.7%, respectively. Jaw involvement of brown tumor is rare. Histopathologically, extensive bone resorption is noted along with the presence of reactive granulation tissue, multiple osteoclasts, hemorrhagic areas, and hemosiderin deposits. Here, we report the case of a brown tumor involving the maxillofacial bone of a 36-year-old male CKD patient with SHPT. Considering the age, sex, and site predilection, this case report is unique.